Factors and Processes of Racialization in the Canadian Academe - Zuhra Abawi (Canadian Society for Studies in Education, 2018)
Although university student demographics have become increasingly racialized and Indigenous, faculty members across Canadian universities do not reflect such demographic shifts (Henry & Tator, 2009). The vast majority of tenured faculty and institutional leaders remain white and male, while an increasing number of precarious sessional faculty are racialized or Indigenous. Further, universities in Canada operate on the narrative of white settler-colonial imperialism rooted in European Enlightenment traditions. In this position paper, I draw on my own experiences as a racialized woman working as a sessional faculty member in Ontario universities. I draw on the theoretical frameworks of Critical Race Theory (CRT) and Tribal Critical Race Theory (TribalCrit) to situate my experiences, and I offer a discussion and review of the literature examining the ongoing barriers and suggestions for resistance to factors and processes of white hegemony embedded in the Canadian academy.